The New “Faces” ("Mianzi", 面子) of Chinese people in Spain: Reciprocity and Market - Moraga Reyes, Jorge (Revista de Antropología Social, 2012)
Among Chinese immigrants in Spain, there exists a distinction whether they are coming from Wenzhou port or Qingtian mountain range, both neighbor locations in the province of Zhejiang and main migratory cores towards the Iberian Peninsula. Starting from this identity distinction, I analyze the presence of “ethnic” reciprocity structures inside the transnational migratory space that are favoring the entry of immigrants into instrumental and consumption rationality patterns. In this article I focus on one of them: mianzi (面子) or face, main source of symbolic capital and the base of the status among Chinese people. I present some of the configurative institutions of mianzi and of the legitimacies that build its value. Despite its entrante in western modernity, mianzi appears as a resourceful structure adapting to new social spaces through the comprehensive meanings and practices that it covers.